Two new species and some new records of Darwin wasps (Hymenoptera: Ichneumonidae) from northwest of Iran - Karimi, Soroush; Ghassemi-Kahrizeh, Akbar; Hosseinzadeh, Abbas; Lotfalizadeh, Hossein; Riedel, Matthias; Mohammadi-Khoramabadi, Abbas (Zootaxa, 2024)
During a survey of the family Ichneumonidae in northwestern Iran, a total of 17 species belonging to the subfamilies Banchinae, Cryptinae, Ichneumoninae, Mesochorinae, Metopiinae, Orthopelmatinae, Phygadeuontinae and Tersilochinae were identified. Two species, Lissonota (Lissonota) rufofacies Riedel nov. sp. and Orthopelma mukriyana Riedel nov. sp. are new to science and are described and illustrated. Their diagnostic characters are provided. We also provide collecting details for the fifteen species recorded for the first time from Iran.